2015
DOI: 10.1093/pch/20.8.e43
|View full text |Cite
|
Sign up to set email alerts
|

Service utilization in a sample of preschool children with autism spectrum disorder: A Canadian snapshot

Abstract: Although most preschool children with ASD residing in urban centres were able to access specialized services shortly after diagnosis, marked variation in services across provinces remains a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Available data suggest that nearly 40% of families affected by autism do not have access to any services around the time of diagnosis (Volden et al 2015). The lack of enactment mechanisms may explain why the same barriers to access to services have been reaffirmed over the past 6 years, including long wait times for diagnostic and intervention services, poor care coordination across different levels of service, and inadequate support for caregivers.…”
Section: Action and Enactment Of Policymentioning
confidence: 99%
“…Available data suggest that nearly 40% of families affected by autism do not have access to any services around the time of diagnosis (Volden et al 2015). The lack of enactment mechanisms may explain why the same barriers to access to services have been reaffirmed over the past 6 years, including long wait times for diagnostic and intervention services, poor care coordination across different levels of service, and inadequate support for caregivers.…”
Section: Action and Enactment Of Policymentioning
confidence: 99%
“…Although they showed that use of services differed by socioeconomic characteristics, the children in the sample already had a diagnosis of ASD and their enrollment in an ongoing study meant that they differed considerably from children in the general population, who face substantial barriers to receiving care. A study in Canada found that behavioral interventions were reported for 28% of children at a baseline visit and that the proportion increased to 59% in the following 12 months (18). A large survey of children with special health care needs found that 38% to 44% of children identified as having ASD received community-based behavioral interventions (19).…”
mentioning
confidence: 99%
“…[ 1 ] Although some ASDs patients might be able to live independently, a large proportion of them has to face social deficits with impairment of skills/emotion, or severe disabilities necessitating lifelong care, and support services. [ 3 6 ] ASDs not only significantly restrict the ability of a person to perform routine activities and contribute to the society, but even remarkably reduce the educational and employment options for the affected person. [ 5 6 ]…”
mentioning
confidence: 99%
“…[ 3 6 ] ASDs not only significantly restrict the ability of a person to perform routine activities and contribute to the society, but even remarkably reduce the educational and employment options for the affected person. [ 5 6 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation